2018
DOI: 10.1007/978-3-319-76270-8_39
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional Video in Museums – Authentic, Immersive and Entertaining

Abstract: Omnidirectional video (ODV) provides possibilities for capture and presentation of cultural content for museums and other exhibitions. 360° video capture can record authentic environments and activities, and enables immersive viewing of such material. We present the potential of ODV by reporting the learnings from long-term user experience data collection with two ODV-based museum installations; a head mounted display (HMD) based rally simulator, and a road grader simulator utilizing three projectors and hapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…These innovative implementations have revealed that users are willing to have multisensory experiences in CH contexts [5], as they have good impressions of multisensory interactions [11], they have increased feelings of presence [12] and they feel more involved during their visits [13]. Regarding the overall multisensory experiences, good results have been demonstrated regarding satisfaction [11]- [17], sense of presence (or immersion) [14], [15], [17]- [19], acquired knowledge and interpretation [15], [18], and value of the experience in different dimensions such as quality of the experience [11], [16], [17] or intercultural exchange [9].…”
Section: Introductionmentioning
confidence: 99%
“…These innovative implementations have revealed that users are willing to have multisensory experiences in CH contexts [5], as they have good impressions of multisensory interactions [11], they have increased feelings of presence [12] and they feel more involved during their visits [13]. Regarding the overall multisensory experiences, good results have been demonstrated regarding satisfaction [11]- [17], sense of presence (or immersion) [14], [15], [17]- [19], acquired knowledge and interpretation [15], [18], and value of the experience in different dimensions such as quality of the experience [11], [16], [17] or intercultural exchange [9].…”
Section: Introductionmentioning
confidence: 99%
“…Only 3 participants had watched 360° videos several times while almost half (11) had watched them a couple of times at most. The rest had only heard/read about them (6) or had no experience at all (4). Earlier experience with virtual reality technologies in general was also rather limited: Only 1 had used such technologies a lot, 7 a couple of times at most and the rest had even less or had no experience on VR technologies, such as VR glasses.…”
Section: Participantsmentioning
confidence: 99%
“…Using an HMD is an immersive and enjoyable way of viewing 360° videos [10] [14]. Such setups have already been used in countless contexts, such as collaborative wayfinding activities [9], industrial maintenance tasks [20], cinematic virtual reality [4] [18] [19], and recreational simulator experiences [6] [20].…”
Section: Introductionmentioning
confidence: 99%
“…O FTEN digital representations of inaccessible locations, rare cultural events and remote touristic destinations [5], [16] are used to provide users with impressions which would be hard to obtain in reality. In recent years, such digital representations have frequently either been interactive and stereoscopic virtual environments (VE) or spherical videos.…”
Section: Introductionmentioning
confidence: 99%